Diseño de un plan estratégico para la empresa comercial Viserco comercializadora de productos de bazar y -papelería en el distrito metropolitano de Quito - Marcillo Meza, María Eugenia (2013)
In the company "Commercial Viserco" proposes to develop a strategic plan design and has no formal planning their activities, leading to stagnation by the management company that currently manages empirical, harming their development and business growth. Throughout the project implementation plan was structured based on the description of the processes in each of the areas as well as the current system handled, which provided meet the different activities and goals of the company, thus allowing how to perform the actions that lead strategic analysis, as they were, the formulation of the mission and vision, formulating strategic objectives, conducting internal and external audits to identify opportunities, threats, strengths and weaknesses, and then make a strategies and finally develop action plans that will contribute to reach the strategic objectives set.